Coupled flight dynamics and CFD analysis of pilot workload in ship airwakes - (:unkn) unknown (American Institute of Aeronautics and Astronautics Inc., 2007)
This paper describes a recent investigation of the helicopter/ship dynamic interface, in which pilot workload is examined using a novel coupling of flight dynamics and CFD analysis. This fully coupled method uses preexisting flight dynamics and CFD analysis codes, running concurrently; the two codes share data, with the flight dynamics code providing position and loading data and the CFD analysis code providing local velocity data. Results obtained using the fully coupled method are compared to results with no coupling, one-way coupling, where the flight dynamics code uses precalculated airwake solutions, and flight test data. Analysis of the time history and frequency domain results and the CFD solutions shows that the one-way coupling method can predict a level of pilot workload equal to or greater than that of the fully coupled method for the cases simulated. The addition of the rotor downwash to the CFD solution in the fully coupled method shows that vortices in the airwake that have a significant effect in one-way coupling may have either a similar effect or a lessened effect if the vortices are pushed away from the helicopter.